2022
DOI: 10.1016/j.psj.2021.101587
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation method of the poultry house indoor environment based on gray relation analysis and analytic hierarchy process

Abstract: Due to the antagonism and synergy among environmental factors in the poultry house, the influence process becomes extremely complex. As a result, it is difficult to predict and evaluate the degree of such influence accurately. In this paper, we study the poultry house environment factor and its relationship with poultry production performance, using the gray relation analysis ( GRA ) to filtrate the main factors that influence the evaluation of the poultry house environment. Put forward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Owing to its flexibility about the analysis of the expert preferences without considering the type of scale, it maintains the stability even if the range of standards and alternatives is wide. They validated the advantages of MARCOS methodology compared to traditional multi-criteria techniques including: Multi-Attributive Border Approximation area Comparison (MABAC) 26 , Additive Ratio Assessment (ARAS) 27 , Weighted Aggregated Sum Product Assessment (WASPAS) 28 and TOPSIS 29 . MARCOS has been successfully applied in different areas by considering the above-mentioned examples from the literature.…”
Section: Proposed Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Owing to its flexibility about the analysis of the expert preferences without considering the type of scale, it maintains the stability even if the range of standards and alternatives is wide. They validated the advantages of MARCOS methodology compared to traditional multi-criteria techniques including: Multi-Attributive Border Approximation area Comparison (MABAC) 26 , Additive Ratio Assessment (ARAS) 27 , Weighted Aggregated Sum Product Assessment (WASPAS) 28 and TOPSIS 29 . MARCOS has been successfully applied in different areas by considering the above-mentioned examples from the literature.…”
Section: Proposed Methodsmentioning
confidence: 92%
“…Its core includes the index system of the evaluated object and the selected evaluation method 24 . At present, the Multi-Criteria Decision-Making (MCDM) method corresponds to a powerful tool being widely used for comprehensive evaluation, such as analytic hierarchy process (AHP) 23 27 , entropy weight (EW) 25 28 , cloud method (CM) 24 , 28 , grey relation analysis (GRA) 29 , analytic network process (ANP) 30 32 , Decision Making Trialand Evaluation Laboratory (DEMETEL) 31 – 35 , Više-Kriterijumska Optimizacija I Kompromisno Rešenje (VIKOR) 33 – 39 , and technique for order of preference by similarity to ideal solution (TOPSIS) 28 , 36 – 39 evaluation method based on evidence theory. These MCDM evaluation methods are currently being used for ranking of indicators, risk identification and evaluation, sustainable development evaluation between countries, economic evaluation, social evaluation, environmental protection evaluation, technical evaluation, and other issues.…”
Section: Introductionmentioning
confidence: 99%
“…maintains its stability even if the range of standards and alternatives is wide. They showed that the advantages of the MARCOS methodology with traditional multi-criteria techniques: Multi-Attributive Border Approximation area Comparison (MABAC) 23 , Additive Ratio Assessment (ARAS) 24 , Weighted Aggregated Sum Product Assessment (WASPAS) 25 and TOPSIS 26 . MARCOS has been successfully applied in many different areas by considering the above-mentioned examples from the literature.…”
Section: The Marcos Methodsmentioning
confidence: 99%
“…Its core includes the index system of the evaluated object and the selected comprehensive evaluation method 21 . At present, the Multi-Criteria Decision-Making (MCDM) method is a powerful tool to widely used for comprehensive evaluation, such as analytic hierarchy process (AHP) [20][21][22][23][24] , entropy weight (EW) [22][23][24][25] , cloud method (CM) 21,25 , grey relation analysis (GRA) 26 , analytic network process (ANP) [27][28][29] , Decision Making Trialand Evaluation Laboratory (DEMETEL) [28][29][30][31][32] , Više-Kriterijumska Optimizacija I Kompromisno Rešenje (VIKOR) [30][31][32][33][34][35][36] , technique for order of preference by similarity to ideal solution (TOPSIS) 25,[33][34][35][36] evaluation method based on evidence theory. These MCDM evaluation methods are currently used in the ranking of indicators, risk identification and evaluation, sustainable development evaluation between countries, economic evaluation, social evaluation, environmental protection evaluation, technical evaluation and other issues.…”
Section: Introductionmentioning
confidence: 99%
“…Its core consists of the evaluation object's index system and the thorough evaluation method chosen [47]. The MCDM method is currently a powerful tool for comprehensive evaluation, such as Analytic Hierarchy Process (AHP) [48], Entropy Weight (EW) [49], Cloud Method (CM) [50], Grey Relation Analysis (GRA) [51], Analytic Network Process (ANP) [52], Decision Making Trialand Evaluation Laboratory (DEMETEL) [53], Više-Kriterijumska Optimizacija I Kompromisno Rešenje (VIKOR) [54], Technique for Order Performance by Similarity to Ideal Solution (TOPSIS) [55] evaluation method based on evidence theory. There are several applications for the MCDM evaluation methods currently in use, including the ranking of indices, the identification and evaluation of risk and the comparison of sustainable development between nations as well as economic, social, environmental, and technical assessments.…”
Section: Introductionmentioning
confidence: 99%